2009
DOI: 10.1177/000313480907500911
|View full text |Cite
|
Sign up to set email alerts
|

Resection of Portovenous Structures to Obtain Microscopically Negative Margins during Pancreaticoduodenectomy for Pancreatic Adenocarcinoma is Worthwhile

Abstract: Locally advanced pancreatic adenocarcinoma may require resections of the portal vein and/or its major tributaries to achieve tumor extirpation, albeit with the potential for increased morbidity and mortality. However, major venous resections can impart complete tumor extirpation and thereby a survival advantage compared with resections with residual microscopic disease. This study was undertaken to determine if resection of the portal vein and/or its splenic or superior mesenteric venous (SMV) tributaries is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 28 publications
1
25
0
1
Order By: Relevance
“…Many case series have documented the feasibility of MVR during a Whipple procedure to remove cancer invading the veins 1–18 . The approaches used to achieve these resections were developed independently within centres with specific interest in locally invasive cancers of the pancreas.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Many case series have documented the feasibility of MVR during a Whipple procedure to remove cancer invading the veins 1–18 . The approaches used to achieve these resections were developed independently within centres with specific interest in locally invasive cancers of the pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the literature is characterized by important differences in whether and how study variables are reported, in staging methods and in techniques of pathologic evaluation of specimens. For instance, many studies report the incidence of R1 resections, 5,9,10,13,14,16,23–29 but few report the method used to determine resection margin status 5,16,27–29 . Only a minority of papers report using a specific system to analyse pathology specimens.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations